The influence of work motivation on employee performance: Case study at PT Pertamina International Refinery RU III Plaju - Rozi, Fahrur; Widiyanti, Marlina; Yusuf, M; Hadjri, Muhammad Ichsan (International research journal of management, IT and social sciences, 2024)
This study aims to analyze the effect of work motivation on employee performance at PT Kilang Pertamina Internasional RU III Plaju, the largest oil processing company in Indonesia that faces competitive challenges in the global energy industry. Work motivation is identified as one of the main factors that influence the success of employees in carrying out their duties and responsibilities, and directly impacts the achievement of company goals. This research method uses primary data obtained through questionnaires filled out by 148 company employees, then processed with a Likert scale and statistical analysis. The results showed that work motivation has a significant influence on employee performance, with a correlation coefficient of 0.773. With good motivation, employees tend to be more productive, focused, and committed to work, thus supporting the achievement of organizational goals.